Robust, high-speed intra-vehicular communication networks for the vehicles of tomorrow - Basford, M.J. (2021)
Cars of the 21st century are increasingly reliant upon computers for the most basic of applications. Whether it is safety-critical, such as the transfer of a braking command, or the more banal adjustment of a music playback device, cars have not escaped the relentless tide of digital dominance. As the trend for a higher degree of automation in everyday cars continues, this phenomenon shows little sign of abating soon. However progress must not come about at the expense of safety. As the metal bars that once linked pedals to brakes were strong to ensure reliable operation, so too must we ensure data networks transfer signals reliably. Traditional means of ensuring the integrity of data on networks utilise shielded conductors, adding both mass and cost to vehicles. This work presents an overview of contemporary intra-vehicular communication networks and presents the following new and novel findings: 1. A comprehensive survey of the intra-vehicular electromagnetic environment of a fully autonomous, electric vehicle. 2. The discovery of a complex relationship between the bit error ratio and time-domain interference which can be used to design networks with greater data throughput and resilience to interference. 3. The replication of the intra-vehicular environment for the development and verification of a wireless intra-vehicular communication system. These findings challenge some existing practices regarding data integrity design methods as well as investigate the feasibility of removing wired communication links from intra-vehicular networks.